A model for harnessing the power of the mobile phone technology to improve smallholder agriculture in Zimbabwe - Musungwini, Samuel (Karlstad University, 2018)
Mobile technologies are capable of facilitating networks of farmers and agribusiness in a dynamic way such that these stakeholders can support each other. The initiative of using mobile technologies in agriculture is in its infancy stage in the world at large while in some developing countries it is already in use. The smallholder farmers largely depend on agricultural activities for food and income for all their requirements which include paying school fees for children, buying farming implements for next season and housekeeping requirements. The bulk of small scale farming systems in the developing world are very much limited in production and therefore inherently less profitable than they should be. The chief contributor to this is the information lopsidedness and the necessary farming skills gap that hinder the embracing of available technologies and management practices. This paper designs a model that could be used for harnessing the power of Mobile Phone Technology to improve Smallholder Agriculture in Zimbabwe. An analysis of the current array of models was done and their weaknesses evaluated. The proposed model is holistic in nature and build on the strength of current existing models but it stresses the need to integrate USSD technology, together with web-enabled and Android based platforms. It also stresses the need for a hybrid mechanism for data dissemination which facilitates for both push-based and pull-based data dissemination